Novel concepts and improvisation for treating postpartum haemorrhage: a narrative review of emerging techniques - G. J. Hofmeyr (BMC, 2023)
Abstract Background Most treatments for postpartum haemorrhage (PPH) lack evidence of effectiveness. New innovations are ubiquitous but have not been synthesized for ready access. Narrative review Pubmed 2020 to 2021 was searched on 'postpartum haemorrhage treatment', and novel reports among 755 citations were catalogued. New health care strategies included early diagnosis with a bundled first response and home-based treatment of PPH. A calibrated postpartum blood monitoring tray has been described. Oxytocin is more effective than misoprostol; addition of misoprostol to oxytocin does not improve treatment. Heat stable carbetocin has not been assessed for treatment. A thermostable microneedle oxytocin patch has been developed. Intravenous tranexamic acid reduces mortality but deaths have been reported from inadvertent intrathecal injection. New transvaginal uterine artery clamps have been described. Novel approaches to uterine balloon tamponade include improvised and purpose-designed free-flow (as opposed to fixed volume) devices and vaginal balloon tamponade. Uterine suction tamponade methods include purpose-designed and improvised devices. Restrictive fluid resuscitation, massive transfusion protocols, fibrinogen use, early cryopreciptate transfusion and point-of-care viscoelastic haemostatic assay-guided blood product transfusion have been reported. Pelvic artery embolization and endovascular balloon occlusion of the aorta and pelvic arteries are used where available. External aortic compression and direct compression of the aorta during laparotomy or aortic clamping (such as with the Paily clamp) are alternatives. Transvaginal haemostatic ligation and compression sutures, placental site sutures and a variety of novel compression sutures have been reported. These include Esike's technique, three vertical compression sutures, vertical plus horizontal compression sutures, parallel loop binding compression sutures, uterine isthmus vertical compression sutures, isthmic circumferential suture, circumferential compression sutures with intrauterine balloon, King's combined uterine suture and removable retropubic uterine compression suture. Innovative measures for placenta accreta spectrum include a lower uterine folding suture, a modified cervical inversion technique, bilateral uterine artery ligation with myometrial excision of the adherent placenta and cervico-isthmic sutures or a T-shaped lower segment repair. Technological advances include cell salvage, high frequency focussed ultrasound for placenta increta and extra-corporeal membrane oxygenation. Conclusions Knowledge of innovative methods can equip clinicians with last-resort options when faced with haemorrhage unresponsive to conventional methods.